Assessment and management of white mullet Mugil curema (Valencienne, 1836) (Mugilidae) fisheries of the south coast of São Paulo state, Brazil - Mendonça,JT. (2011)
There is intense fishing activity, mainly artisanal, in the Cananéia, Iguape and Ilha Comprida Estuarine System. White mullet (Mugil curema) is one of the local fishery resources and is usually caught with gillnets and fish traps. This study aimed to characterise the Mugil curema fisheries thereby underpinning the management of the species in the region. The study was developed with data collected from landings in the town of Cananéia, São Paulo state, Brazil, from 1995 to 2009. Production data, fishing effort and CPUE were used to assess the evolution of captures. The gillnets were characterised by interviewing fishermen from 16 communities in Cananéia. White mullet fishery has aroused the interest of fishermen in the region since the 80s and today it is one of the main products of artisanal estuarine fishery off the south coast of São Paulo. The major landings occur in the warmer months with fish traps and gillnets being the main fishing gear used. The largest catches occur in the spawning months of the species from October to April. The highest landings varied according to different fishing gear, showing differences primarily due to trade preferences and to the structure of the fishing gear. According to the index of abundance used in this study, the resource is overfished due to the progressive increase in fishing effort, so it is suggested that measures should be taken to control fishing effort, such as special fishing permits to catch white mullet, especially with gillnets. The current management measures neither meet the needs of fishermen nor the preservation of the resource, and must be reviewed in a participatory way with management agencies and the fishery sector, ensuring greater legitimacy and success in the sustainability of the activity.